Gender Inequality across Time and Space in Myanmar - Khine, ohmar (Thailand and The World Economy, 2025)
This study assesses the evolution of gender equality between 1973 and 2019 under military and non-military regimes in Myanmar. Gender inequality remains a significant barrier in Myanmar: women have participated in major political events since 1974 but have failed to gain equality in politics, health, education, or economic development. Past reports on this issue lacked quantitative analyses due to information inaccessibility. Also, these reports assumed a homogeneous population in Myanmar. In this study, the Gender Inequality Index was calculated empirically from various data sources at different periods and regions. Independent variables such as health, education, regional economic development, ethnicity, and urbanization were disaggregated at the state, division, and township levels. We controlled unobserved factors across time by using a time-fixed effect and across space by using a state-fixed effect in the specification. The results showed that gender inequality was 5 percent higher (p < 0.01) during the military regime than during the non-military periods. Also, it was higher in the northwestern borders than in other areas but much lower in the Yangon Division and parts of Mon State. These results provide a detailed view of the factors that influence gender inequality and may assist in planning social and economic programs at the granular level in Myanmar.